2013
DOI: 10.1080/08927014.2013.777954
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alginate oligosaccharides on the mechanical properties of Gram-negative biofilms

Abstract: The influence of a novel, safe antibiofilm therapy on the mechanical properties of Pseudomonas aeruginosa and Acinetobacter baumannii biofilms in vitro was characterized. A multiscale approach employing atomic force microscopy (AFM) and rheometry was used to quantify the mechanical disruption of the biofilms by a therapeutic polymer based on a low-molecular weight alginate oligosaccharide (OligoG). AFM demonstrated structural alterations in the biofilms exposed to OligoG, with significantly lower Young's modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 41 publications
2
62
0
Order By: Relevance
“…The viscosity of biofilm samples was measured using a Physica MCR 301 rheometer (Anton Paar). Biofilms of WT and CP2-1-S1 were prepared by dropping 100 l of overnight cultures (OD 600 , ϳ1.5) onto 0.45-m filter membranes (diameter, 87 mm; Schleicher & Schuell, Dassel, Germany), placing them on MM1 agar, and incubating them at 30°C for 24 h. The membranes with biofilms were then transferred to the rheometer, and the viscosity of each biofilm was determined as previously described (30,31).…”
Section: Methodsmentioning
confidence: 99%
“…The viscosity of biofilm samples was measured using a Physica MCR 301 rheometer (Anton Paar). Biofilms of WT and CP2-1-S1 were prepared by dropping 100 l of overnight cultures (OD 600 , ϳ1.5) onto 0.45-m filter membranes (diameter, 87 mm; Schleicher & Schuell, Dassel, Germany), placing them on MM1 agar, and incubating them at 30°C for 24 h. The membranes with biofilms were then transferred to the rheometer, and the viscosity of each biofilm was determined as previously described (30,31).…”
Section: Methodsmentioning
confidence: 99%
“…OligoG CF-5/20 is currently in phase 2b clinical trials in CF patients. Previous in vitro studies have shown the ability of OligoG CF-5/20 to perturb biofilm formation, thereby reducing tolerance to antibiotic treatment (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Flos lonicerae, Wuwei xiaodu pulvis, Shuanghuanglian, Chinese gallnut extract and ginseng monomer [40][41][42] have the effect of inhibiting or destroying the biofilm. The bacteriophage AB7-IBB1, AB7-IBB2 and OligoG [27,[43][44][45] can promote dissociation and release of biofilm. Nanoparticles break the existing mechanism of resistance, including the reduction of drug absorption and the inhibition of the formation of Acinetobacter baumannii biofilm.…”
Section: Destruction Of the Formed Biofilm Of Acinetobacter Baumanniimentioning
confidence: 99%